Global patterns of power sector reform, 1982–2013 - Johannes Urpelainen; Joonseok Yang (Energy Strategy Reviews, 2019)
A reliable supply of electricity is essential for economic development, and developing countries across the world have implemented reforms to improve their power sector performance. We publish a dataset of power sector reforms in 142 developing countries from 1982 to 2013 and use the data to describe patterns of variation. We find that privatization and liberalization of competition continue to lag behind other reforms, such as allowing independent power producers and establishing electricity regulators. However, this gap is only wide for relatively poor and authoritarian countries with low institutional capacity. Hybrid power markets remain a reality, but economic growth and democratization can move power sectors in emerging economies to a different direction. If developing economies continue to expand their economies, build state capacity, and move toward democratic political institutions, then we may see more private electric utilities and competition for profits in the future. Keywords: Political economy, Power sector, Policy reform, Developing countries